ADOPSI DAN IMPLEMENTASI KECAKAPAN LITERASI INFORMASI DAN LITERASI DIGITAL UNTUK AKSELERASI UMKM DI INDONESIA PASCA PANDEMI COVID-19 - Purwanto Putra; Andi Windah; Ana Tarisa (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Ilmu Budaya, UIN Sunan Kalijaga Yogyaka, 2021)
Almost all countries in the world are facing the Covid-19 pandemic, which is spreading so massively. Affecting various aspects of life and causing a domino effect in many sectors including the economy. Indonesia's economy worsened in the second quarter (Q2) 2020, negative 5.32 percent and only started to recover in the second quarter of 2021, positive 7.07% thanks to investment and increased household consumption. The MSME sector plays a significant and strategic role in supporting and is predicted to be the engine of economic recovery after the Covid-19 pandemic. The positive contribution of MSMEs to GDP before the pandemic could reach almost 60%. However, now in a condition full of uncertainty, it is necessary to strengthen various ideas, innovations and collaboration of various parties so that MSMEs can get out of pressure and support economic growth. This study will look at the potential for the adoption and implementation of digital literacy skills and information literacy by involving librarians (library institutions), academics, and literacy activists supporting MSMEs in contributing to economic recovery after Covid-19. This study uses a qualitative-descriptive approach in order to present a detailed description of the setting and literacy skills for MSME actors. This research is general in nature (generalization) with the scope of its location in Indonesia, without mentioning specific areas. Primary sources of research are obtained from literature studies, studies of various media and journal articles which are assumed to be able to capture the general condition of society. The results show that the idea of adopting and implementing digital literacy skills and information literacy for MSME actors has an urgency to be implemented immediately as a solution to the challenges of possible innovation (behavior) changes in the habits and operations of the MSME sector after Covid-19. Accelerate the transformation of MSMEs through strengthening the digital literacy and information literacy sectors to support MSME business functions (production, promotion, and marketing) after Covid-19.